Mixed adenoneuroendocrine carcinoma in gallbladder with ovarian metastasis of adenocarcinoma component: A case report (Indian Journal of Case Reports, 2025)
Mixed adenoneuroendocrine carcinoma (MANEC) are uncommon tumors exhibiting both adenocarcinomatous and neuroendocrine differentiation with both components constituting at least 30% of the total cellular population. We report a case of a 39-year-old lady, presenting as a case of Krukenberg’s tumor, and the primary was found to be in the gallbladder which on pathological examination revealed a MANEC.